Penerapan Prinsip Good Governance dalam Pelayanan Publik di Desa Taluduyunu dan Taluduyunu Utara Kecamatan Buntulia Kabupaten Pohuwato - Pakaya, Melki; Djaafar, Lucyane; Alhamid, Saleh (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the application of good governance principles in public services in Taluduyunu Village and North Taluduyunu, with a focus on the aspects of transparency, accountability, and responsiveness. This study uses a descriptive qualitative approach with data collection methods through interviews, observations, and documentation. The results of the study indicate that the application of the three principles in both villages has not been running optimally. In terms of transparency, the village government is expected to be more open in conveying information to the public, especially regarding budget management and work programs. In terms of accountability, the role and responsibility of the village government, especially the village head, still need to be improved so that program implementation can be accounted for more optimally. Meanwhile, the responsiveness of the village government to the needs and input of the community is also considered to still need to be considered and strengthened through more effective service and communication mechanisms. In general, the results of this study indicate the need to increase the commitment and capacity of village officials in implementing the principles of good governance to realize better public services.